PERANCANGAN WEDDING MAGAZINE PERNIKAHAN ADAT MINANGKABAU DI KOTA PADANG - ANOM JUHARDA, Drs. M. Nasrul Kamal, M.Sn, Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
The purpose of the design Wedding Ceremony Wedding Magazine Minangkabau in the city of Padang is to determine the design of Minangkabau Wedding Magazine Wedding Ceremony in the City. Methods of data collection in the design of this thesis is to field observations, interviews, and sources of data and information from print media to analyze the strengths, weaknesses, opportunities, and threats. The results showed that the design elements used in the mainstream media covers images, text, and narration refers to the concept of verbal and visual concepts. Application layout or layout of the major media and supporting media refers to the principles of design elements desaian in order to get good results. Thus the design Wedding Magazine. Traditional wedding in the city of Padang Minangkabau visualization of images in the media and its supporting media can promote the procedures for Wedding Ceremony in the city of Padang Minangkabau of West Sumatra.Kata Kunci : Perancangan, Wedding Magazine